Three-dimensional thermal management: Biomass aerogel with super-hydrophilicity for high-efficiency solar evaporation via environmental energy synergy - Li Jiang; Yanyou Huang; Liangdong Ye; Yuling Lv; Ruibin Shen; Wei Wang; Yanlan Pan; Zuocai Zhang; Shaorong Lu (Desalination, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

Seawater eDNA and Underwater Visual Surveys Reveal Genus-Level Reef-Building Coral Communities in the Wanshan Archipelago, South China Sea - Jiabin Guo; Lan Yang; Zhihui Qin; Anxin Lu; Yuling Ma; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang; Kefu Yu; et al. (Fishes, 2026)
Environmental DNA (eDNA) metabarcoding is increasingly used as a complementary tool for coral biodiversity assessment, but its performance in subtropical, estuary-influenced reef systems remains insufficiently tested. This study combined seawater eDNA metabarcoding with concurrent underwater visual surveys and historical records to assess reef-building scleractinian corals in the Wanshan Archipelago, Pearl River Estuary. In June 2022, surface and bottom seawater samples were collected from seven sites, yielding 14 eDNA samples, and dive-based photographic surveys were conducted concurrently. A universal 18S rRNA assay was used for high-throughput sequencing, and eDNA detections were compared with visual and historical survey data at the genus level. eDNA detected 13 families and 21 genera, with Porites and Echinopora as dominant genera. eDNA recovered more genera than concurrent visual surveys in all five regional comparisons, although the two methods yielded overlapping but partly distinct genus inventories. Surface-water eDNA showed a slight, site-dependent advantage in genus recovery and overlap with concurrent visual surveys, whereas correspondence with historical records varied among regions; surface and bottom samples shared most genera but also contributed complementary layer-specific detections. Community composition showed spatial clustering broadly consistent with geographic proximity. These findings indicate that seawater eDNA provides complementary genus-level information and support paired surface- and bottom-water sampling for a more complete exploratory characterization of coral diversity in complex subtropical coastal reef systems.

The Identification of Digramma interrupta (Diphyllobothriidae: Ligula) in a Captive Red-Crowned Crane and a Crucian Carp Reveals a New Case for Co-Occurrence - Maolin Lu; Yuling Yang; Mengchao Zhou; Yaxian Lu; Honyan Yu; Ruisi Zhang; Tianlu Liu; Mengru Zhao; Lei Han; Zhijun Hou (Acta Parasitologica, 2026)

Sustainable and multifunctional organohydrogel integrating high strength, environmental resilience, and humidity sensitivity for smart healthcare monitoring - Ruibing Shen; Yanyou Huang; Li Jiang; Yuling Lv; Zuocai Zhang; Liangdong Ye; Ziwei Li; Shaorong Lu (Chemical Engineering Journal, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

Stretchable multifunctional composite films with ultra-high conductivity for sustainable heating, EMI shielding, and antimicrobial applications - Yuling Lv; Yanyou Huang; Liangdong Ye; Ruibing Shen; Li Jiang; Wei Wang; Shaorong Lu (Chemical Engineering Journal, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Biomass organohydrogel toward green wearable sensors: Enhancing high and low temperature sensing properties, UV shielding properties, and long-term cycling durability - Ruibing Shen; Qiaoyan Wei; Liangdong Ye; Liling Zhang; Yanyou Huang; Yuling Lv; Ziwei Li; Zuocai Zhang; Xiaokun Han; Shaorong Lu (Chemical Engineering Journal, 2026)

Dynamic Changes in Serum Biochemical Indices and Alternative Splicing Events Revealed Molecular Regulatory Mechanisms in Rainbow Trout Under Copper Stress - Junhao Lu; Jinqiang Quan; Jing Zhou; Yucai Pan; Jiahui Zhang; Ziguo Wang; Yuling Qu (Marine Biotechnology, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

Preparation of omniphobic membrane by anchoring hydrophobic islands at fixed-points for treating hypersaline wastewater - Ronghua Ma; Xiaolong Lu; Jie Gu; Kai Ren; Yuling Ren; Yuefei Song; Zhong Ma (Desalination, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

Elemental composition of non-nest soil, nest soil, and ant bodies in globally invasive ant species Solenopsis invicta and Tapinoma melanocephalum across various habitats - Yuling Liang; Mingrong Liang; Yunbo Song; Jingxin Hong; Huimei Chen; Syed Arif Hussain Rizvi; Yongyue Lu (Science of The Total Environment, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Impact of electric vehicle downsizing on shared mobility considering externalities - Li Li; Yuling Shi; Dianchao Lin; Yongliang Lu (Transportation Research Part D: Transport and Environment, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Natural selection of Lacticaseibacillus paracasei mutant: Weaken the post-acidification of fermented milk - Lei Li; Han Lu; Yuling Xue; Yannan He; Baohua Zhao; Lianzhong Ai; Shijie Wang (Food Bioscience, 2025)

Functional analysis of (E)-β-farnesene synthases involved in accumulation of (E)-β-farnesene in German chamomile (Matricaria chamomilla L.) - Yuling Tai; Haiyan Wu; Lu Yang; Yi Yuan; Youhui Chen; Honggang Wang; Yifan Jin; Luyao Yu; Shuangshuang Li; Feng Shi (Plant Science, 2025)

Collagen IV/laminin-1 coated temozolomide-prodrug hydrogel for recruiting and eradicating residual glioma cells - Yufu Zhu; Jiaqi Jin; Yang Lu; Diancheng Hang; Xuefeng Zhang; Gang Zhao; Qing Wang; Yuling Li; Hongmei Liu (Chemical Engineering Journal, 2025)

Evaluation of the efficacy of disinfectants and disinfection methods against Ascaris suum eggs - Ruisi Zhang; Maolin Lu; Hongyan Yu; Tianlu Liu; Zhiying Cui; Yuling Yang; Mengchao Zhou; Yaxian Lu; Hang Tian; Lihong Tian; Lei Han; Zhijun Hou (Veterinary Parasitology, 2024)

Correction: Identification and biochemical characterization of a novel halolysin from Halorubellus sp. PRR65 with a relatively high temperature activity - Yuling Hao; Yu Jin; Aodi Zhang; Xinran Jiang; Ming Gong; Cunlong Lu; Ruru Pan; Shaoxing Chen (World Journal of Microbiology and Biotechnology, 2024)

Secondary flexural behaviour of reinforced concrete beams strengthened with special-shaped rivet bonded steel plates and prestressed CFRP bars - Yuling Zhou; Xuesong Lu; Tingzhen Ming (European Journal of Environmental and Civil Engineering, 2024)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

Identification and biochemical characterization of a novel halolysin from Halorubellus sp. PRR65 with a relatively high temperature activity - Yuling Hao; Yu Jin; Aodi Zhang; Xinran Jiang; Ming Gong; Cunlong Lu; Ruru Pan; Shaoxing Chen (World Journal of Microbiology and Biotechnology, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

Protective effects of the secondary metabolites from Quercus salicina Blume against gentamicin-induced nephrotoxicity in zebrafish (Danio rerio) model - Shuang-Hui Yin; Wen-Jun Zhang; Lu-Lu Jiang; Guang-Yue Wang; You-Jin Jeon; Yuling Ding; Yong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Drought- induced decrease in tree productivity mainly mediated by the maximum growth rate and growing-season length in a subtropical forest - Zheqi Zhang; Lingyan Zhou; Chunyan Lu; Yuling Fu; Zhizhuang Gu; Yang Chen; Guodong Zhang; Xuhui Zhou (Forest Ecology and Management, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Near-full-length genome analysis of two novel HIV second recombinant forms in Hebei, China - Yuxin Feng; Jianhua Lu; Lijing Wang; Yuling Wang; Jingyun Li; Hanping Li; Lin Li; Erhei Dai (Archives of Virology, 2024)

Genomic, Physiological, Biochemical, and Phenotypic Evidences Reveal a New Species, Halomicroarcula salaria sp. nov - Tao Hong; Juntao Ke; Liangzhon Chen; Yuling Hao; Peng Lu; Shaoxing Chen (Current Microbiology, 2024)

Unlocking the carbon emission efficiency improvement path of technological innovation: a perspective on industrial restructuring and R&D element flows - Shimei Weng; Weiliang Tao; Yuling Lu (Environmental Science and Pollution Research, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Nanozyme-mediated biocatalysis as a mitochondrial oxidative stress amplifier for tumor nanocatalytic immunotherapy - Junya Lu; Luming Song; Shuaipeng Feng; Kaili Wang; Yuling Mao; Yikun Gao; Qinfu Zhao; Siling Wang (Chemical Engineering Journal, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Correction: The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

Numerical simulation of proppant transportation and placement in several complex structure fractures of a shale reservoir using a CFD approach - Mingliang Luo; Guoxu Jia; Yuling Yang; Xiaodong Si; Yunzhi Ge; Yongping Zhan; Mingjing Lu (Gas Science and Engineering, 2023)

Quantitative Assessment of Monitoring Natural Attenuation on Carbon Tetrachloride Reduction at a Groundwater-Contaminated Site in Eastern China - Yaqiang Wei; Weijiang Liu; Ling Liu; Haobo Niu; Lu Li; Yuling Chen; Jian Chen (Water, Air, & Soil Pollution, 2023)

Intergenerational effects of parental [Cnmim]BF4 (n = 4, 6, 8) ionic liquids exposure on zebrafish development based on transcriptomic analysis - Yue Liu; Yanan Tian; Chenning Zhang; Xin Lu; Yuling Xue; Xinping Wang; Qiuyue Liao; Xin Li; Kai Lian; Jiaolong Huang; Jie Deng; Peng Duan (Science of The Total Environment, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Mineral-microbial interactions in nine-year organic fertilization field experiment: a mechanism for carbon storage in saline-alkaline paddy soil - Mengmeng Chen; Yuling Zhang; Chunwei Gao; Shirong Zhang; Lu Liu; Lipeng Wu; Yuyi Li; Xiaodong Ding (Plant and Soil, 2023)

hsa_circ_0000417 downregulation suppresses androgen receptor expression and apoptotic signals in human foreskin fibroblasts via sponging miR-6756-5p - Junqiang Huang; Cheng Su; Pingan Lu; Xiangyou Zhao; Yuling Liu; Qike Xie; Chao Chen (Molecular Biology Reports, 2023)

The effect of chlorfenapyr exposure on Solenopsis invicta Buren (Hymenoptera: Formicidae) - Yuling Liang; Mingrong Liang; Panpan Li; Yunbo Song; Yongyue Lu (Journal of Asia-Pacific Entomology, 2023)

Social carrying capacity and emotion dynamics in urban national parks during the COVID-19 pandemic - Xiao Xiao; Jie Gao; Junyu Lu; Peizhe Li; Yuling Zhang (Journal of Outdoor Recreation and Tourism, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

The comparative impact among different intensive statins and combination therapies with niacin/ezetimibe on carotid intima-media thickness: a systematic review, traditional meta-analysis, and network meta-analysis of randomized controlled trials - Hongwei Li; Xiaolin Xu; Liming Lu; Runlu Sun; Qi Guo; Qian Chen; Junjie Wang; Zhijian He; Yuling Zhang (European Journal of Clinical Pharmacology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Whether foreign direct investment can promote high-quality economic development under environmental regulation: evidence from the Yangtze River Economic Belt, China - Xiaosheng Li; Yuling Lu; Ruting Huang (Environmental Science and Pollution Research, 2021)

Interleukin-25 in sputum as a marker of airway inflammation in children asthma - Yun Zhang; Cuifen Zhao; Xiuxia Zhao; Qingyu Kong; Mingjie Ding; Yuling Han; Xiang Ma; Lu Cheng (Science China Life Sciences, 2019)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

High glucose induced rat aorta vascular smooth muscle cell oxidative injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Yan Zhang; Zhonghong Gao (Journal of Physiology and Biochemistry, 2011)

High glucose induced human umbilical vein endothelial cell injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Hailing Li; Yan Zhang; Zhonghong Gao; Yuefa Gong (Molecular and Cellular Biochemistry, 2008)